Cardiac rehabilitation may not provided a quality of life benefit in coronary artery disease patients - Tavella Rosanna; Beltrame John F (BMC, 2012)
Abstract Background Improvements in patient-reported health-related quality of life (HRQoL) are important goals of cardiac rehabilitation (CR). In patients undergoing coronary angiography for angina and with documented coronary artery disease (CAD), the present study compared HRQoL over 6 months in CR participants and non-participants. Clinical predictors of CR participants were also assessed. Methods A total of 221 consecutive patients undergoing angiography for angina with documented CAD and who were eligible for a CR program were recruited. CR participants were enrolled in a six-week Phase II outpatient CR course (31%, n = 68) within 2 months following angiography and the non-participants were included as a control. At baseline (angiography), one and six months post angiography, clinical and HRQoL data were obtained including the Short Form-36 (SF-36) and the Seattle Angina Questionnaire (SAQ). The response rate for the HRQoL assessment was 68% (n = 150). Cross sectional comparisons were age-adjusted and performed using logistic or linear regression as appropriate. Longitudinal changes in HRQoL were assessed using least squares regression. Finally, a multiple logistic regression was fitted with CR participant as the final outcome. Results At angiography, the CR non-participants were older, and age-adjusted analyses revealed poorer physical (angina limitation: 54 ± 25 versus 64 ± 22, p <0.05) and mental HRQoL (significant psycho-social distress: 62%, n = 95 versus 47%, n = 32, p <0.05) compared to the CR participants. In addition, the CR participants were more likely to have undergone angiography for myocardial infarction (OR = 2.8, 95% CI 1.5-5.3, p = 0.001). By six months, all patients showed an improvement in HRQoL indices, however the rate of improvement did not differ between the controls and CR participants. Conclusion Following angiography, CAD patients reported improvements in both generic and disease-specific HRQoL, however CR participation did not influence this outcome. This may be explained by biases in CR enrollment, whereby acute patients, who may be less limited in HRQoL compared to stable, chronic patients, are targeted for CR participation. Further investigation is required so CR programs maximize the quality of life benefits to all potential CR patients.